Full Recovery From Cocaine-Induced Toxic Leukoencephalopathy: Emphasizing the Role of Neuroinflammation and Brain Edema - Edward C. Mader MD; Alexander B. Ramos MD, MS; Roberto A. Cruz MD; Lionel A. Branch MD (SAGE Publishing, 2019)
Toxic leukoencephalopathy (TL) is characterized by white matter disease on magnetic resonance imaging (MRI) and evidence of exposure to a neurotoxic agent. We describe a case of cocaine-induced TL in which extensive white matter disease did not preclude full recovery. A 57-year-old man with substance abuse disorder presented with a 5-day history of strange behavior. On admission, he was alert but had difficulty concentrating, psychomotor retardation, and diffuse hyperreflexia. Brain MRI revealed confluent subcortical white matter hyperintensities with restricted diffusion in some but not in other areas. Electroencephalography (EEG) showed mild diffuse slowing. Blood tests were normal except for mild hyperammonemia. Urine screen was positive for cocaine and benzodiazepine but quantitative analysis was significant only for cocaine. Prednisone 60-mg qd was initiated on day 4, tapered over a 5-day period, and discontinued on day 9. He was discharged after 3 weeks. Cognitive function returned to normal 2 weeks after discharge. Five months later, neurologic exam and EEG were normal and MRI showed near-100% resolution of white matter lesions. TL has been attributed to white matter ischemia/hypoxia resulting in demyelination/axonal injury. The clinical, EEG, and MRI findings and time course of recovery of our patient suggest that cocaine-induced inflammation/edema resulted in TL but not in ischemic/hypoxic injury. While inflammation/edema may have regressed when cocaine was discontinued, we cannot exclude a role for prednisone in protecting the patient from the ischemic/hypoxic sequelae of inflammation/edema. MRI is indispensable for diagnosing TL but EEG may provide additional useful diagnostic and prognostic information.